THE ATTRACTIONS OF GUAR KEPAH ARCHAEOLOGICAL SITE, PENANG, MALAYSIA AS AN ARCHAEOLOGICAL HERITAGE TOURISM SITE - Mohd Hasfarisham ABD HALIM; Shaiful SHAHIDAN; Shyeh Sahibul Karamah MASAN; Mokhtar SAIDIN (Geo Journal of Tourism and Geosites)
The Guar Kepah archaeological site in Penang, Malaysia, has been the focus of archaeological re search since 1860, revealing important insights into the prehistoric maritime community that inhabited the area approximately 5,000 years ago. Excavations at the site have revealed human skeletons, teeth, stone tools, and pottery, providing evidence of the community's burial traditions and material culture. The primary data collected from these excavations has facilitated the development of the site's tourism sector, with plans underway to establish the Guar Kepah Archaeological Center (GKAC). This study emphasises the importance of utilising primary data to create compelling narratives that contribute to the development of archaeological heritage tour packages. The Guar Kepah site serves as a case study for the development of archaeotourism, highlighting the need for a balance between site preservation and providing authentic experience to cultural tourists. The findings from this site have the potential to shed light on human relations with aquatic habitats, the importance of the mari ne environment in human evolution and ecology, island colonisation, and the establishment of maritime trade networks. The development of the Guar Kepah site as an archaeological heritage tourism location in northern Peninsular Malaysia demonstrates the commitment of the government and stakeholders to promoting sustainable heritage tourism in the region.